Frontal mucocele masked as upper lid abcess-a case report - Ng, WL; Umi Kalthum Md Noh; Jemaima Che Hamzah; Norshamsiah MD (Faculty of Medicine, UKM Medical Centre, 2016)
Frontal mucocele is not commonly masked as upper lid abscess.A 72-year-old Chinese man with underlying hyperthyroidism complained of left upper eyelid swelling of 6 months duration. The swelling had persisted and worsen when intravenous antibiotic was changed oral type. Visual acuity on presentation was hand motion and reverse relative afferent pupillary defect was present. Because the swelling was large and resulted in mechanical ptosis and ophthalmoplegia, a CT imaging was performed, which showed huge left frontal mucocele eroding the supereromedial orbital rim. The left globe was displaced inferolaterally but there was no extension into brain parenchyma. Fundus examination showed pale optic disc with dull macula. Old laser marks were seen at peripheral fundus. Referral to ortholaryngologist was made and endoscopic sinus surgery and evacuation of mucopyocoele was done. Culture and sensitivity of the fluid showed no organism. He recovered well postoperatively with additional two weeks of antibiotics. We highlight the necessity of surgical drainage of mucocele, following a course of antibiotic.